The Influence of Internal Environmental Capabilities on Sustainable Competitive Advantage through Green Innovation with Corporate Reputation Moderation: A Study on Natural Dye Batik SMEs in Yogyakarta - Sabrina, Nadia (International Journal Labs, 2024)
This study aims to analyze the influence of internal environmental capabilities on sustainable competitive advantage mediated by green innovation and the role variable of corporate reputation that affects the relationship between green innovation and sustainable competitive advantage. This study uses a quantitative method with a survey research design. The research sample is 72 batik SMEs with natural dyes in the Special Region of Yogyakarta. Data analysis uses the smartPLS 4.0 technique. The results of the study show that there is an indirect influence between the ability of the internal environment to sustainable competitive advantage, namely through the variable of green innovation. This study did not find any direct influence between internal environmental capabilities and sustainable competitive advantage. Furthermore, another finding is that the Company's reputation strongly influences the relationship between green innovation and sustainable competitive advantage. These findings have implications for practitioners to develop green innovations to achieve sustainable competitive advantages for their SMEs.